淸熱音樂療法을 適用하는 韓方音樂治療에 관한 硏究 - Lee Seung-hyun(李承鉉); Kim Yeo-jin(金儷眞) (대한한의학원전학회지, 2009)
The purpose of this study is to introduce heat-clearing music therapy[淸熱音樂療法] as one of the 17 kinds of oriental medicine music therapy. The heat-clearing music therapy[淸熱音樂療法] can be applied to certain types of syndromes. The representative syndromes are flaring-up of the heart Fire[心火], rising of the liver Yang[肝陽], and fidgetiness due to deficiency of Eum(陰, Yin). Metal-Gi[金氣] music and Water-Gi[水氣] music are mainly used in heat-clearing music therapy, The patients with the case of flaring-up of the heart Fire[心火] may listen to Metal-Gi[金氣] music. For the patient with rising of the liver Yang[肝陽], relieving constraint music therapy can be used. In other cases with patients with fidgetiness due to deficiency of Eum, replenishing vital essence music therapy can be used. This study describes the theory of heat-clearing music therapy[淸熱音樂療法] that has a good possibility as a new method of oriental medical treatment. KCI Citation Count: 4